Live yeast (Saccharomyces cerevisiae) improves growth performance and liver metabolic status of lactating Hu sheep - Shendong Zhou; Jie Huang; Hao Zhang; Xiaokun Song; Yijin Jiang; Xu Zhao; Xiangzhen Shen (Journal of Dairy Science)
ABSTRACT: Yeast, a natural starter culture, is widely used to improve digestion function in ruminants. However, whether yeast affects the physiological state of the liver in ruminants is currently unknown. The aim of this study was to investigate the effects of yeast on liver metabolic status and physiological functions of Hu sheep during lactation. A total of 24 lactating Hu sheep were randomly divided into 4 groups with 6 sheep in each group: the control group (normal diet) and the low-, medium-, and high-dose groups, in which each sheep was fed an additional 0.5 g, 1 g, and 2 g yeast per morning, respectively. Blood, liver, small intestine samples were collected for subsequent analysis, and milk production and BW were recorded during the experimental period. The results showed that dietary yeast supplementation mitigated BW loss, enhanced liver function, and increased milk protein and lactose contents in Hu sheep during lactation. Compared with the normal diet, dietary yeast supplementation reduced the content of lipid droplets in the liver, significantly upregulated the expression of lipid β-oxidation-related enzymes (PPARA and CPT1A), and significantly decreased the expression of lipid synthesis-related enzymes (FASN, PPARγ, DGAT1, and DGAT2) in the liver without affecting the capacity of the small intestine to absorb foodborne lipids. In addition, dietary yeast supplementation significantly decreased blood nonesterified free fatty acid content and increased blood glucose and liver expression of key enzymes involved in gluconeogenesis (PCK1α, FBP, and G6PC). These results suggest that dietary yeast supplementation may alleviate weight loss and enhance milk quality in Hu sheep during lactation. Furthermore, it can improve liver metabolic adaptability and protect liver health by regulating lipid metabolism and metabolic glucose homeostasis in the liver. Notably, adding 1 g or 2 g of yeast to the daily diet yields superior effects.